PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, DEWAN DIREKSI DAN DEWAN KOMISARIS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN CONSUMER GOODS TAHUN 2019-2021 - Fatmawati, Sinta; Alliyah, Siti (Jurnal Riset Mahasiswa Akuntansi, 2023)
This study aims to determine the effect of capital structure, company size, board of directors and board of commissioners on financial performance. The population in this research is consumer goods companies that are listed on the IDX in 2019-2021. The sampling technique used was purposive sampling so that a sample of 81 samples was obtained. The data analysis technique used to test the hypothesis is multiple linear regression analysis using SPSS. The results of this study indicate that capital structure has a significant negative effect on financial performance, the board of directors has a significant positive effect on financial performance, company size and the board of commissioners have a non-significant negative effect on financial performance.